Surgical Correction of Different Severities of Astigmatism Using Wavefront-Optimized Photorefractive Keratectomy - Sharghi, Afshan; Ojaghi, Habib; Yavari, Saba; Zahirian Moghadam, Telma (International Journal of Psychosocial Rehabilitation, 2020)
Background and Objective: Astigmatism is a prevalent refractive error. One of the most common methods of refractive surgery is photorefractive keratectomy (PRK) surgery. The aim of this study is to determine the effectiveness of PRK on three types of astigmatism (mild, moderate, and severe). Methods: This prospective interventional case series was performed on 46 eyes of 25 patients with astigmatism ranging from 1 to 6 diopters with ≤1D sphere. After obtaining informed written consent, demographic information of patients and the results of the examination were recorded. The patients undergoing surgery were followed up for 12 months, and their data were then collected and statistically analyzed. Results: The mean preoperative and postoperative refractive astigmatism was -3.01±1.42 and -0.40±0.37 (D), respectively (p<0.001). The mean preoperative and postoperative sphere was also -0.12±0.51 and -0.00±0.16 (D), respectively (P=0.11). While the mean preoperative refractive astigmatism in the severe, moderate, and mild groups was -5.00±0.57 (D), -3.27±0.49 (D), and -1.79±0.42 (D), respectively, the mean postoperative refractive astigmatism in the severe, moderate, and mild groups was -0.70±0.45 (D), -0.37±0.37 (D), and -0.26±0.21 (D), respectively. The effect of PRK on astigmatism correction in severe astigmatism was better than in mild and moderate astigmatism (p<0.001). There was no significant relationship between age and correction of refractive astigmatism using PRK (p=0.75). In addition, refractive stability and keratometric astigmatism were achieved at 3 and 1 month postoperatively, respectively. The mean SIA and IOS were also 3.11±1.52 and 0.14±0.08, respectively. Conclusion: PRK with Allegretto WaveLight Eye-Q 400 is a successful surgery to correct and decrease all types of astigmatism. The RPK effect on the severe astigmatism was significantly higher than mild and moderate types.